Building and brand recognition of veterinary clinics in Slovenia - Jagodič, Gregor (Mednarodno inovativno poslovanje, 2026)
Purpose of the article – The article examines brand development and recognition among veterinary clinics in Slovenia. It understands the veterinary clinic brand not merely as a visual or promotional element, but as the result of professional quality, trust, communication, user experience, and digital presence. Research methodology – The study combines a literature review with a qualitative approach. The empirical component comprises nine semi- structured interviews with owners of private veterinary clinics across Slovenia. Data were analysed using reflexive thematic analysis. Findings – Veterinary clinic owners associate brand development with professional work, treatment quality, operational consistency, clear communication, and user experience. Recognition is linked to local presence, recommendations, professional reputation, a clear clinic identity, and digital visibility. Trust connects brand and recognition, while digital presence supports first contact, accessibility, and perceived credibility.
Keywords: blagovna znamka; brand; brand recognition; communication; digital presence; digitalna prisotnost; komunikacija; prepoznavnost blagovne znamke; uporabniška izkušnja; user experience; veterinarske klinike; veterinary clinics